Solve for x and y
y = 4x+2
y = -2x - 3
[tex]x = \frac{-5}{6}[/tex] and [tex]y = \frac{-4}{3}[/tex]
Given equations are:
y = 4x+2 --------- eqn 1
y = -2x - 3 ---------- eqn 2
We have to solve both equations and find values of "x" and "y"
Substitute eqn 1 in eqn 2
4x + 2 = -2x - 3
Combine like terms we get,
4x + 2x = -3 - 2
On solving,
6x = -5
[tex]x = \frac{-5}{6}[/tex]
Substitute "x" value in eqn 1
[tex]y = 4(\frac{-5}{6}) + 2\\\\y = \frac{-20}{6} + 2\\\\y = \frac{-20 + 12}{6}\\\\y = \frac{-8}{6} = \frac{-4}{3}[/tex]
Thus [tex]x = \frac{-5}{6}[/tex] and [tex]y = \frac{-4}{3}[/tex]